Physical and nutritional properties of Malaysian avocado (Persea americana Mill) fruit - Tan, Chin Xuan; Chong, G. H.; Hamzah, Hazilawati; Mohd Ghazali, Hasanah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
The tropical climate, along with abundant of rainfall throughout the years, produces a wide diversity of succulent and edible fruits in the Malaysia. In Malaysia, avocado (Persea americana Mill) is an underutilized fruit grown in semi-wild conditions of the rural areas or in the small orchards along with other commercial fruit trees. As the global market for avocado fruit is increasing, the underutilized avocado has the potential to be developed as a new commercial fruit crop in Malaysia. Since data on the physical and nutritional properties of Malaysian avocado fruit are necessary for the food industry to determine which part of the fruit can be used for commercialization, a study was conducted with this aim in mind. Results indicated the Malaysian avocado is a medium sized fruit with an average mass, length and diameter of 216.92 g, 9.50 cm and 7.20 cm, respectively. The major part of Malaysia avocado fruit is the pulp (56.01%), followed by the seed (33.04%) and the peel (10.94%). Each of these parts was further investigated for their nutrient composition. All the fruit parts were found to be low in protein (< 1%), but high with moisture content (> 60%). Compared to the peel and seed, the pulp has the highest lipid content (20.79 ± 0.27%), but the lowest ash (1.47 ± 0.13%) and carbohydrate (3.39 ± 0.76%) contents. Malaysian avocado fruit, particularly the pulp, contains a significant amount of lipid content, suggesting the potential for extraction of an edible oil.